Urinary troponin concentration as a marker of cardiac damage in pregnancies complicated with preeclampsia. (November 2020) - Potkonjak, Ana Meyra; Sabolović Rudman, Senka; Nikolac Gabaj, Nora; Kuna, Krunoslav; Košec, Vesna; Stanec, Zdenko; Zovak, Mario; Tučkar, Neven; Djaković, Ivka; Prkačin, Ingrid; Svaguša, Tomo; Bakoš, Matija
Abstract: Pregnant women with preeclampsia experience significant hemodynamic changes which lead to an increased myocardial workload. In response to increased demands in pregnancy, the heart muscle responds with ventricular remodeling process which involves cardiac muscle hypertrophy. Opposed to occurrence of eccentric ventricular hypertrophy in normal pregnancy, myocardial remodeling in a form of concentric hypertrophy will occur in pregnant patients with preeclampsia. Increased myocardial workload is manifested by an increased troponin release. As process of troponin degradation continue, filtration of degradation fragment through glomerular membrane occur, raising the possibility of it's detection in urine. Degradation fragments of troponin molecules are estimated to be 20 kDa with preserved immunoreactivity to high-sensitivity assays. Some of the authors suggest that serum levels of cardiac troponin I might be elevated in patients with hypertension, as well as in preeclamptic pregnant women. It is to be expected that evaluation of severity of the myocardial damage in pregnant woman with preeclampsia may be performed by measuring levels of troponin in the urine using high-sensitivity assays. Designing of urine dipstick will help to detect an early phase of myocardial involvement in preeclamptic pregnancies.